EXPLORING THE EXPENDITURE ON MARKETING IN SOUTH AFRICAN MEDICAL SCHEMES - Willie, Michael Mncedisi (International Journal of Research -GRANTHAALAYAH, 2023)
This review explores the expenditure on marketing in South African medical schemes, which provide healthcare coverage to members in exchange for premium payments. The marketing services offered by these schemes aim to raise awareness, communicate value propositions, target specific demographics, educate, and inform, engage members, and ensure compliance and ethics. The study investigates the variations in marketing expenses based on scheme size, market position, and marketing objectives. It also examines the relationship between marketing costs and membership growth. Transparency, regulation, and improved reporting of marketing activities in the financial statements of medical schemes are highlighted as crucial. Key recommendations include establishing Key Performance Indicators KPIs between schemes and service providers, separating payment for performance indicators from member transfer costs, and collaborating with relevant regulatory bodies to protect consumer interests. The study also suggests maintaining marketing and distribution expenses below certain thresholds and registering and regulating entities involved in marketing-related services. Proposed regulatory bodies for collaboration include the Advertising Regulatory Board, National Consumer Commission, Consumer Goods and Services Ombudsman, and Independent Communications Authority of South Africa. By addressing these issues, medical schemes can enhance the effectiveness of their marketing efforts, improve member value, and ensure compliance with regulatory requirements.